Information available on the internet about pain after orthognathic surgery: A careful review - Pithon,Matheus Melo (2014)
OBJECTIVE: Investigate the quality of data available on the internet with respect to pain after orthognathic surgery.METHODS: A careful search was conducted on the Internet in December, 2012. The most accessed websites browsers were employed for research using the terms: "pain" and "orthognathic surgery" together. The first 30 results of each portal were examined, and after applying the exclusion criteria, 29 sites remained. All remaining websites went through an evaluation process with online tools that investigated the quality, level of reading, accessibility, usability and reliability.RESULTS: Assessment criteria outcomes were considered unfavorable. Texts were considered difficult to read with inappropriate language for the general public. The mean global validation for the 29 websites of the LIDA instrument was 65.10, thereby indicating a structure of medium quality.CONCLUSION: Information about post-orthognathic surgery pain available on the internet is poorly written and unreliable. Therefore, candidates for orthognathic surgery must seek information from specialists who, in turn, should indicate reliable sources.